Indications and outcomes of intraocular lens exchange at a tertiary ophthalmic center in Northern China from 2016 to 2024 - Zhizhong Wu; Baoyue Zhang; Zhimin Chen; Caijuan Liu (Scientific Reports)
Abstract To report the indications and outcomes of intraocular lens (IOL) exchange at a tertiary referral center in northern China over a period of 8 years. Setting: Ophthalmology departments of Hebei Eye Hospital, Hebei, China. Design: Retrospective cross-sectional study. In this retrospective study, the medical records of 233 patients with a history of IOL exchange were reviewed between 2016 and 2024. These cases were reviewed to determine surgical indications, the type of intraocular lens removed, the type of intraocular lens implanted, the time between operations, surgical complications, and visual outcomes. All postoperative data were analyzed at least six months after follow-up. The mean age of our participants was 50.05 ± 21.76 years (range 5–82 years), with a male percentage of 65.67%. The mean time between primary surgery and IOL exchange was 6.64 ± 6.16years (range 0.01–30 year). The main indications of IOL exchange were IOL dislocation (63.37%) and IOL opacification (21.81%). The most common ophthalmic comorbidity was high myopia. Procedures for secondary IOL implantation were scleral fixated IOL with sutures (34.16%), IOL in ciliary sulcus (26.75%), in-the-bag IOL (26.31%) and Iris fixation IOL (7.82%). The mean postoperative corrected distance visual acuity (CDVA) was significantly higher compared to the mean preoperative CDVA (p = 0.00). The mean preoperative and postoperative IOP were 16.23 ± 4.92 and 14.84 ± 3.05 mmHg, respectively (p = 0.00). No serious complications ware observed. IOL dislocation is the most common indication of intraocular lens implantation, followed by IOL opacification. Simultaneous scleral-sutured fixation after IOL replacement is the most common procedure in secondary IOL implantation.